AS REPERCUSSÕES DO ENEM NO CURRÍCULO DO ENSINO MÉDIO DAS ESCOLAS ESTADUAIS NO MARANHÃO: o caso do CINTRA. - MARTINS, Dayse Marinho (2019)
Study on the repercussions of the ENEM in the curriculum of the High School of the state schools in São Luís - MA, having as an intentional sample of research, the Integrated Center of Rio Anil (CINTRA). The purpose of this study was to analyze the repercussions of the ENEM logic on the organization of the school curriculum in aspects such as: calendar, school routine, content selection, teaching methodology and learning evaluation. The study was based on the Historical-Dialectical Materialism by the concept of ideology according to Marx, of a curriculum according to Sacristán and Goodson and tradition invented by Hobsbawn and Ranger. The research is qualitative, guided by the critical-dialectic method, encompassing bibliographic research on specialized literature in High School, curriculum and ENEM as well as documentary research with Brazilian Education Laws and bases, regulations and decrees obtained in the Digital Library of the National Library and in the application Planalto Legis of the Civil House of the Presidency of the Republic, in addition to the reference matrix of the ENEM and curricular guidelines of the state network of Maranhão. In the contextualization of the analysis, a field research was carried out at the CINTRA, involving interviews with managers, coordinators, teachers and focal groups with students of the morning and night shifts, as well as scientific observation and analysis of the curricular organization through documents such as political-pedagogical project and teaching plans. The research focused on the problematization of the curriculum from the ENEM in the state education network of Maranhão, corroborating the perception of the curriculum as a field of political forces, evidencing the contradictions that permeate the offer of High School in the structural duality of Brazilian society. The study showed in CINTRA, repercussions of the ENEM's logic regarding the organization of the curriculum, revealing the need to redefine such an approach in addition to actions focused on student preparation for the exam, fostering interdisciplinarity and problematization. In addition, it made it possible to perceive the progress of conservatism in relation to the ENEM and the necessary resistance of the educators to measures that could disfigure potential approaches to the construction of a critical education.